Partial liquid ventilation for preventing death and morbidity in adults with acute lung injury and acute respiratory distress syndrome - Galvin, Imelda M (Cochrane Database Syst Rev, 2013)
BACKGROUND: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are syndromes of severe respiratory failure that are associated with substantial mortality and morbidity. Artifical ventilatory support is commonly required and may exacerbate lung injury. Partial liquid ventilation (PLV) has been proposed as a less injurious form of ventilatory support for these patients. Although PLV has been shown to improve gas exchange and to reduce inflammation in experimental models of ALI, a previous systematic review did not find any evidence to support or refute its use in humans with ALI and ARDS. OBJECTIVES: The primary objective of this review was to assess whether PLV reduced mortality (at 28 d, at discharge from the intensive care unit (ICU), at discharge from hospital and at one, two and five years) in adults with ALI or ARDS when compared with conventional ventilatory support. Secondary objectives were to determine how PLV compared with conventional ventilation with regard to duration of invasive mechanical ventilation, duration of respiratory support, duration of oxygen therapy, length of ICU stay, length of hospital stay, incidence of infection, long‐term cognitive impairment, long‐term health related quality of life, long‐ term lung function, long‐term morbidity costs and adverse events. The following adverse events were considered: hypoxia (arterial PO(2) <80 mm Hg), pneumothorax (any air leak into the pleural space requiring therapeutic intervention), hypotension (systolic blood pressure < 90 mm Hg sustained for longer than two minutes or requiring treatment with fluids or vasoactive drugs), bradycardia (heart rate < 50 beats per minute sustained for longer than one minute or requiring therapeutic intervention) and cardiac arrest (absence of effective cardiac output). SEARCH METHODS: In this updated review, we searched the Cochrane Central Register of Controlled Trials (CENTRAL Issue 10, 2012, in The Cochrane Library; MEDLINE (Ovid SP, 1966 to November 2012); EMBASE (Ovid SP, 1980 to November 2012) and CINAHL (EBSCOhost,1982 to November 2012) for published studies. In our original review, we searched until May 2004. Grey literature was identified by searching conference proceedings and trial registries and by contacting experts in the field. SELECTION CRITERIA: As in the original review, review authors selected randomized controlled trials that compared PLV with other forms of ventilation in adults (16 y of age or older) with ALI or ARDS, reporting one or more of the following: mortality; duration of mechanical ventilation, respiratory support, oxygen therapy, stay in the intensive care unit or stay in hospital; infection; long‐term cognitive impairment or health‐related quality of life; long‐term lung function or cost. DATA COLLECTION AND ANALYSIS: Two review authors independently evaluated the quality of the relevant studies and extracted the data from included studies. MAIN RESULTS: In this updated review, one new eligible study was identified and included, yielding a total of two eligible studies (including a combined total of 401 participants). Of those 401 participants, 170 received 'high'‐dose partial liquid ventilation (i.e. a mean dose of at least 20 mL/kg), 99 received 'low‐dose' partial liquid ventilation (i.e. a dose of 10 mL/kg) and 132 received conventional mechanical ventilation (CMV). Pooled estimates of effect were calculated for all those who received 'high'‐dose PLV versus conventional ventilation. No evidence indicated that 'high'‐dose PLV either reduced mortality at 28 d (risk ratio (RR) 1.21, 95% confidence interval (CI) 0.79 to 1.85, P = 0.37) or increased the number of days free of CMV at 28 d (mean difference (MD) ‐2.24, 95% CI ‐4.71 to 0.23, P = 0.08). The pooled estimate of effect for bradycardia in those who received PLV was significantly greater than in those who received CMV (RR 2.51, 95% CI 1.31 to 4.81, P = 0.005). Pooled estimates of effect for the following adverse events－hypoxia, pneumothorax, hypotension and cardiac arrest－all showed a nonsignificant trend towards a higher occurrence of these events in those treated with PLV. Because neither eligible study addressed morbidity or mortality beyond 28 d, it was not possible to determine the effect of PLV on these outcomes. AUTHORS' CONCLUSIONS: No evidence supports the use of PLV in ALI or ARDS; some evidence suggests an increased risk of adverse events associated with its use.